Intestinal obstruction in pregnant women. Case report - Apaza, John (2015)
A case of intestinal obstruction with sigmoid colon volvulus in a 14-weeks pregnant woman is presented. This is a rare complication of difficult diagnosis; and the case reported was due to an internal hernia. Some aspects of pathophysiology and diagnosis are discussed.